Butinage - Gez, Yonatan; Droz, Yvan; Rey, Jeanne; Soares, Edio (University of Toronto Press, 2023)
Based on comparative ethnographic research in four countries and three continents, Butinage: The Art of Religious Mobility explores the notion of "religious butinage" as a conceptual framework intended to shed light on the dynamics of everyday religious practice. Derived from the French word butiner, which refers to the foraging activity of bees and other pollinating insects, this term is employed by the authors metaphorically to refer to the "to-ing and fro-ing" of believers between religious institutions. Focused on urban, predominantly Christian settings in Brazil, Kenya, Ghana, and Switzerland, Butinage examines commonalities and differences across the four case studies and identifies religious mobility as existing at the located at the meeting points ofbetween religious-institutional rules and narratives, local social norms, and individual agency and practice. Drawing on aAnglophone, fFrancophone, and lLusophone academic traditions, Butinage this monograph is dedicated to a dialogue between ethnographic findings and theoretical ideas,, and explores how we may rethink common conceptions of religious normativity.